A review on promising phytochemical, nutritional and glycemic control studies on Moringa oleifera Lam. in tropical and sub-tropical regions - Muhammad Irfan, Hafiz; Asmawi, Mohd Zaini; Abdul Karim Khan, Nurzalina (Elsevier, 2016)
Plants have provided sources to find novel compounds. These plants are being used as therapeutic purposes since the birth of mankind. The traditional healers normally utilize medicinal plants as crude drugs while scientists using the folk claim as guides to explore medicinal plants. Moringa oleifera is a famous edible plant having therapeutic and nutritive values. The present study was designed to cumulate the research data regarding to what extent, phytochemical, nutritional and glycemic control studies has been explored using its different extracts. The articles indicated that the powder, aqueous, methanol and ethanol extracts of Moringa oleifera (leaves, pods, seeds, stem and root bark) have significant therapeutic herbal potential to treat diabetes mellitus. Collectively, the mechanism behind is intestinal glucose inhibition, insulin release as well as decrease in insulin resistance probably regeneration of b-cells of pancreas, increase in glutathione and reduction in malondialdehyde. Conclusively, this article give descriptive information about antidiabetic effect, claimed marker compounds and proposed antihyperglycemic mechanism of a single plant. It can be suggested a potential herbal source to treat diabetes mellitus as being widely accepted by major population as nutrition and therapeutic agent.